Chitosan-based biocompatible dressing for treatment of recalcitrant lesions of cutaneous leishmaniasis: A pilot clinical study - Abdollahimajd, Fahimeh; Moravvej, Hamideh; Dadkhahfar, Sahar; Mahdavi, Hamid; Mohebali, Mehdi; Mirzadeh, Hamid (Indian journal of dermatology, venereology, and leprology, 2019)
Background: Chitosan has a biocompatible, biodegradable and nontoxic nature. The effectiveness of nano-chitosan films in the treatment of cutaneous leishmaniasis has been confirmed previously in susceptible laboratory animals. Aims: The aim of this study is to evaluate the safety and efficacy of a chitosan-based biocompatible dressing in patients with cutaneous leishmaniasis who were either nonresponsive to or had medical contraindications for conventional treatments. Materials and Methods: A total of 10 eligible patients were included in this single arm, single center study. The sterile chitosan film was immersed in saline serum and was cautiously extended over the wound to avoid air occlusion. Sterile Vaseline gauze was then applied and the film was kept on the wound site for 7 days and was repeated every week until the healing was completed. Complete clinical response was defined as complete re-epithelialization of the skin lesion as well as microscopic negative results for amastigote forms of Leishmania sp. Results: All patients showed either significant (30%) or complete (70%) improvement after 8 weeks of therapy and at 16 weeks post treatment all cases were completely cured. It was well tolerated and there were no product-related adverse events such as allergic reaction or infection. Moreover, no recurrences were observed in any patients after 6 months follow-up. Limitations: The lack of a control group, relatively small sample size and failure to evaluate the histological and molecular effects of chitosan were the limitations of this study. Conclusion: Our findings confirmed that chitosan can be safely and effectively used for the treatment of cutaneous leishmaniasis. We were unable to find any previous clinical study in evaluating the efficacy of chitosan for cutaneous leishmaniasis on human subjects. Further studies are recommended to design a randomized, double-blinded clinical trial with more volunteers who infected with different species of Leishmania and various clinical forms of cutaneous leishmaniasis.